Static tensile and fatigue and testing of aluminium plate with holes and cracks - Yeap, Shi Hong (2011)
In an aircraft structure, fatigue failures usually started from the initiation and propagation of cracks from notches or defects. For example, an aircraft usually has a lot of rivet holes. High stress concentrations are usually found on these holes and these are the likely places for the development of cracks. These cracks can propagate with elliptic or near-elliptic crack fronts. To prevent catastrophic failures, it is important that we study the behaviour of the crack growth and apply the necessary repairs before the structure fails. This project sets to predict the crack propagation of cracks in holes via experimental methods. The material used for investigation was Al7075-T651 Aluminium Alloy and two centre holes with cracks on them were drilled in the centre of the specimens. Tensile tests were conducted to determine the breaking load of the specimens and a percentage of the breaking load was used for fatigue tests. Different percentages of the breaking load were used to find out which percentage will give a more accurate result. It was noticed that the fracture surface of the fatigue specimens had a shinier surface than the test specimen itself. In addition, when using a larger percentage of breaking load for the fatigue tests, which results in fewer cycles to failure, it was observed that the results are less accurate whereby the striation markings started too far away from the initial crack. As a result, the initial stages of crack propagation could not be observed.